Analysis of axial thermal conductivity of dual-porosity fractal porous media with random fractures. (November 2016) - Miao, Tongjun; Cheng, Sujun; Chen, Aimin; Yu, Boming
Highlights: A novel model for thermal conductivity of dual-porosity media is derived based on fractal geometry theory. The analytical expression for thermal conductivity is found to be a function of the fractal dimensions and the microstructural parameters of the media. The model predictions are in good agreement with the available experimental data. Abstract: Heat transfer in porous media has received steady attention in many applications such as in energy, aerospace, biomedicine and chemical engineering. In this work, based on the fractal characteristics of pores and fractures in porous media, the analytical solution of axial effective thermal conductivities is proposed for saturated dual-porosity media. It is found that the proposed axial effective thermal conductivity is a function of geometrical parameters of dual-porosity media, such as the porosities ( ϕ m, ϕ f ), fractal dimensions ( D f, D l ) for porous matrix and fractured network, tortousity fractal dimension ( D T ), and fracture orientation (dip θ, azimuth α ). The effects of the microstructural parameters on the effective thermal conductivity of the media are analyzed systematically. The model predictions are compared with the available experimental data, and good agreement between them is found. The present model may provide a better understanding of the physical mechanisms of heat transfer in dual-porosity media than conventional models.